Primerjalna študija »drobne dramatike« v priročnikih Marije Vide Kovačič - Blažič, Milena (Amfiteater (Ljubljana), 2025)
The article offers the first comprehensive analysis of school drama in postwar Slovenia through the work of Marija Vida Kovačič. By applying a mixed-methods approach that combines qualitative content analysis with quantitative frequency analysis on a corpus of 501 literary units, the study uncovers the structure, authorial repertoire and thematic preferences in the teaching manuals Za celo leto (1960) and Praznični koledar (1976), as well as their connection to her editorial work in Pionirski list. The results reveal a dominance of domestic authors (87%), a deliberate inclusion of female authors (36% among the most productive authors), and the emergence of the concept of “micro-drama” (drobna dramatika): a brief, functionally oriented pedagogical dramatic form. The analysis demonstrates that the work of Marija Vida Kovačič shaped the school cultural programme into a complex cultural-pedagogical project that functioned as a tool for socialisation, cultural development and the formation of collective identity in postwar Slovenia.
Keywords: avtorji; drobna dramatika; Kovačič, Marija Vida; letni koledar; povojna Slovenija; šolska dramatika